2013
DOI: 10.1111/jspn.12010
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis‐related diabetes in older adolescents: Parental support and self‐management

Abstract: Education about CFRD management and support of adolescent autonomy in disease management is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 50 publications
0
47
0
2
Order By: Relevance
“…In the present study, the adolescents had received education regarding CF during childhood; however, the information was not routinely or regularly repeated; therefore, the young adults lacked information about the disease and self-management. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the adolescents had received education regarding CF during childhood; however, the information was not routinely or regularly repeated; therefore, the young adults lacked information about the disease and self-management. 10 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…Health professionals must ensure that young patients master the knowledge and skills essential for self-management of the disease. 10 , 11 , 14 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some viewed their diabetes as an extension of CF, others saw CFRD as a nuisance that could be ignored when the primary challenges of CF escalated, while still others felt that having lived with CF made them better equipped to address diabetes management [7] . These data also revealed that most CF patients were unfamiliar with the possibility of developing diabetes and that many lacked the knowledge and confidence to approach this new chronic illness [6] , [7] , [8] .…”
Section: Introductionmentioning
confidence: 99%
“…Existing reports include few participants diagnosed with CFRD as children [6] , and to our knowledge there have been no studies of how children react to CFRD management. Available data on parental reactions to their child's diagnosis with CFRD are mainly focused on adolescent autonomy [8] . We know very little about the ways in which patients and parents manage CFRD and factors that make adherence more or less difficult.…”
Section: Introductionmentioning
confidence: 99%